The Watty Awards as a Discoverability Tool for Wattpad Authors - Sabo, Oana (Mémoires du livre / Studies in Book Culture, 2025)
This article examines Wattpad’s annual writing contest—the Watty Awards—as a key mechanism of discoverability for Wattpad writers. Launched in 2010 as an informal popularity prize, it has transformed into a coveted award that has led to publicity on the platform as well as publishing and film adaptation deals. My study, which is based on qualitative interviews with Watty Award winners, reveals that being “discovered” translates differently according to factors of language, literary genre, award category, and jury composition. Discoverability, I argue, emerges as a notion in constant transformation due to several forces—Wattpad’s commercial strategies, first and foremost, but also, significantly, the tactics of the award winners themselves.